A prospective non-comparative study to assess the effectiveness and safety of combination laxative therapy containing milk of magnesia, liquid paraffin and sodium picosulphate (Cremaffin-Plus®) in the management of constipation in patients with anal fissure/hemorrhoids/obstructive defecation syndrome - Patankar, Roy; Mishra, Ajeet (International Surgery Journal, 2017)
Background: Assess the effectiveness and safety of combination laxative therapy containing milk of magnesia, liquid paraffin and sodium picosulphate (Cremaffin-Plus®) in management of constipation, in patients with anal fissure/haemorrhoids/obstructive defecation syndrome (ODS). Methods: Patients visiting study site with complaints of constipation secondary to anal fissures/haemorrhoids/ODS, intended to receive combination laxative therapy (as per physicians’ discretion), were enrolled. Primary objectives were to assess the change in number of bowel movements per day and stool consistency; secondary objectives were to assess change in straining, physician global efficacy assessment, quality of life (PAC-QOL score), Constipation Symptoms (CSS), Fecal Incontinence Score (FIS), Patient Assessment of Constipation Symptoms (PAC-SYM) score, along with the Modified Longo Score (MODS) for ODS from baseline to end of 4 weeks. Safety, tolerability and treatment adherence were also assessed. Results: About 32 patients (anal fissure:19, haemorrhoids:5, ODS:8) met inclusion criteria. Significant improvement in stool frequency was observed in all patients pooled together (p=0.016); group wise, statistical significance was noted in patients of anal fissures. Stool consistency was improved in all patients pooled together (p<0.001); group wise, significant improvement was seen in patients of anal fissure and ODS. There was a significant improvement in straining noted in all patients pooled together (p=0.002). Significant reduction (p<0.001) was noted in all the symptom scores (CSS, FIS, PAC-SYM and PAC-QOL) from baseline to 4 weeks in all patients. About 51.44% reduction in MODS score was noted in patients with ODS. Conclusions: Improvement in stool frequency, consistency and straining was noted in all patients with constipation (with fissure/haemorrhoids/ODS) treated with Cremaffin-plus for 4-weeks, improving the quality of life. All patients showed good therapy adherence with better safety and tolerability profile.